Strength anisotropy of shales deformed under uppermost crustal conditions. Issue 1 (7th January 2017) - Bonnelye, Audrey; Schubnel, Alexandre; David, Christian; Henry, Pierre; Guglielmi, Yves; Gout, Claude; Fauchille, Anne‐Laure; Dick, Pierre
Abstract: Conventional triaxial tests were performed on three sets of samples of Tournemire shale along different orientations relative to bedding (0°, 45°, and 90°). Experiments were carried out up to failure at increasing confining pressures ranging from 2.5 to 160 MPa, at strain rates ranging between 3 × 10 −7 s −1 and 3 × 10 −5 s −1 . This allowed us to determine the entire anisotropic elastic compliance matrix as a function of confining pressure. Results show that the orientation of principal stress relative to bedding plays an important role on the brittle strength, with 45° orientation being the weakest. We fit our results with a wing crack micromechanical model and an anisotropic fracture toughness. We found low values of internal friction coefficient and apparent friction coefficient in agreement with friction coefficient of clay minerals (between 0.2 and 0.3) and values of K I c comparable to that already published in the literature. We also showed that strain rate has a strong impact on peak stress and that dilatancy appears right before failure and hence highlighting the importance of plasticity mechanisms. Although brittle failure was systematically observed, stress drops and associated slips were slow and deformation always remained aseismic (no acoustic emission were detected). This confirms that shales are good lithological candidates for shallow crust aseismic creep and slow slip events. Key Points: Triaxial tests performed on Tournemire shale Strong influence of strain rate on mechanical strength Importance of plasticity mechanisms